An investigation into gain and group delay measurement for digital microwave radio - Gammon, Donald Brian (Department of Electrical Engineering, 2026)
Digital Microwave Radio is increasingly replacing analogue systems on line-of-sight microwave links. These systems are particularly susceptible to channel linearity and group delay distortion caused by multipath fading. A simple, inexpensive method of measuring gain and group delay over a link is called for. This is required to have sufficient dynamic range and speed to cover the fast, deep frequency selective fades associated with multipath fading. A brief overview of multipath fading and its measurement is given. The design and construction of a simple, prototype PC-based gain and group delay measurement system for a loop-back arrangement is described. This system is based at the IF frequency. It consists of hardware/software interfaces, an IF frequency synthesizer/generator, gain measurement, group I delay measurement, and control and processing software. The IF frequency is swept over the frequency band, either in a synthesized manner, or in a fast, non-synthesized manner and measurements taken during the sweep. These are displayed by the software. Gain measurement is performed by comparison of amplitudes of the IF signal and group delay measurement by phase comparison of a modulation of the IF signal. A method is given to extend the system to an end-to-end measurement. The existing system is capable of measuring gain and group delay in a loop-back system at the required speed and with the required amplitude range. Some problems exist in the accuracy, range and resolution of the group delay measurements and in the matching for gain measurements. Recommendations are made to correct these in an end-to-end measurement system.